A Survey on Cyber Security Analytics - Sameera, Nerella; Shashi, M (International Journal of Computer Sciences and Engineering, 2025)
Increase in internet dependency in all walks of life, digital nature of data in huge amounts getting accumulated through online transactions and decentralization of data repositories, has led to the development of effective security mechanisms. While discussing the challenges of combating cybercrime, this paper provides a comprehensive overview of cyber security mechanisms, recent attack prediction techniques to create attack prediction models. This paper also explores recent trends in cyber-security like graph data analytics and security in wireless sensor networks. Emerging trends in security system design leveraging social behavioral biometrics, network security analytics, and contextual information to identify known as well as unknown cyber- attacks are also discussed. A framework for contextual information fusion to detect cyberattacks is presented.